The effect of mycorrhizal species on the growth, essential oils, yield and morpho-physiological parameters of Lemon Balm (Melissa officinalis L.) under water-deficit conditions in Tabriz region - Shamizi, Neda; Yarnia, Mehrdad; Mohebalipour , Nasser; Faramarzi, Ali; Ajalli, Jalil (Plant Science Today, 2022)
Two years experiment were conducted in 2016-2017 as split-plot based on randomized completely block design with three replications to morpho-physiological responses of Lemon Balm (Melissa officinalis L.) plant to mycorrhizal fungi species treatments (control, Rhizophagus intraradices, Funneliformis mosseae, Glomus hoi and combined application of all three species) under different irrigation regimes (irrigation after 70, 100, 130 and 160 mm evaporation). In results, the highest oil yield was achieved in irrigation at 100mm+application of all three species of mycorrhizal fungi. Irrigation after 100 mm evaporation increased this trait by 33% compared to irrigation after 70 mm evaporation due to increase in essential oil percentage under dehydration conditions, however, increasing drought stress led to a significant decrease in essential oil yield. In terms of physiological parameters, dehydration led to an increase in proline content and antioxidant activates. In general and according to the results, modifying the destructive effects of water deficit stress and the use of mycorrhiza can increase the essential oil of lemon Balm. But aggravating water deficiency conditions can drastically reduce the essential oil yield. The founds could be helpful for herbal medicine researchers to achieve high-quality drugs.